Mitigating Risk Through Educational Provision For Somali Refugees: The Role Of Fugee School In Gombak, Selangor, Malaysia - Lai, Kien Wee (2018)
Catastrophic event occurred across a wide spectrum of human lives from environment, economics, health and security. World Risk Society thesis viewed the occurrence of the events as risk and threaten the balance of the world. The occurrence of civil war in Somalia have subsequently led to the rise of terrorist activities inciting fear within the state by attacking educational institution which subsequently disrupted the education of school-going children and young adolescent where they eventually leave the state and seek refugee status in transitional countries. However, in Malaysia, the government have no obligation towards refugees as they are not the signatories of the United Nation Convention and Protocol Relating to the Status of Refugees. Refugees are discriminated and exploited by the authorities and illegal employer whilst being denied access to job and education opportunities. Within the world risk society thesis, the sub-politics are those who work beyond the formal political process to achieve their objectives by handling issues neglected by the government. Refugee children and young adolescent educations are stunned as they are not allowed entrance to public school due to lack of documentation, the research examined the Fugee School as sub-politics on educational provision for Somali refugee. The information was collected through in-depth interview and focus group interview with the founder, coordinator, principal, children and young adolescent of the school. Official and news reports along with past literature served as triangulation tools to proof consistencies of the information from interviews.